A time for war [large type] : a thriller - Savage, Michael, 1942- (Center Point Large Print, 2013)
A Chinook helicopter carrying a squad of Navy Seals suddenly plummets to earth in Afghanistan. A car driven by FBI agents tailing a suspicious vehicle is mysteriously rendered immobile in San Francisco. The U.S. is under secret attack and only Jack Hatfield, a popular television host hounded from his position by left-wing forces in the media for speaking the truth, suspects the danger of this lethal conspiracy. With the help of Dover Griffith, an idealistic young woman staffer at the Office of Naval Intelligence, Hatfield pursues a trail leading to a billionaire American electronics entrepreneur who has sold out his own country with the help of officials at the highest level of the American government.